Rehabilitation of Eyelid Malpositions Secondary to Facial Palsy - Şeyda Karadeniz Uğurlu; Mustafa Karakaş (Türk Oftalmoloji Dergisi, 2017)
Objectives: To evaluate patient satisfaction and outcomes of surgical treatment of eyelid malpositions secondary to facial palsy. Materials and Methods: Consecutive patients with facial palsy who underwent surgical treatment by the same surgeon at İzmir Katip Çelebi University Atatürk Training and Research Hospital between Jan 2007 and Dec 2012 were included in the study. Ophthalmic examination findings, surgical approaches, and their outcomes were evaluated. A successful result for upper eyelid position was defined as more than 50% reduction in lagophthalmos and induction of less than 2 mm of ptosis. A successful outcome for lower eyelid position was defined as the lower eyelid residing at or within 1 mm above or below the limbus. Linear visual analog scale 1 (VAS-1) (subjective complaints) and VAS-2 (cosmetic outcome), both ranging from 0 to 10, were used to compare preoperative findings with findings at last postoperative visit. Results: The mean age of the 14 female and 21 male patients was 54.5±19.9 years. Gold weight implantation (n=31), lateral tarsal strip (n=22), tarsorrhaphy (n=15), suborbicularis oculi fat elevation (n=16), hard palate graft (n=14), and eyebrow ptosis repair (n=6) were performed. Average follow-up time was 17.9±16.9 months (range, 2-60). Surgical success rates were 90% for upper lids and 75% for lower lids. Mean lagophthalmos decreased from 7.1±2.7 mm to 1.6±1.6 mm postoperatively (p=0.000). The use of lubricating drops and gels was reduced from average preoperative daily values of 5.3±2.5 drops and 1.3±0.6 gel applications to 4.4±1.4 and 0.6±0.6, respectively (p=0.003, p=0.001). Conclusion: An individualized surgical approach tailored according to each patient’s severity of facial palsy and associated malpositions resulted in both functional and aesthetic improvements in our patients.